Corneal transplant: bioethical aspects - Hurtado Sarrió, Mercedes; Duch Hurtado, Mercedes; Tudela, Julio (Acta Bioethica, 2019)
This paper addresses the bioethical aspects of corneal transplantation, from donation and types of donation, including the trade of organs and tissues, as well as the methodology of transplantation and use of immunosuppressive treatments, in addition to informed consent and patient participation. in decisions. The current techniques are analyzed, the effectiveness and the circumstances in which each of them can be applied as well as the emergent studies based on cell therapy. Some of the studies use stem cells derived from human embryos, and others from adult tissues and induced pluripotent stem cells (iPS). A bioethical analysis of the consequences may arise from the different clinical options available. A bioethical analysis of the consequences that can be derived from the different clinical options available is proposed. Finally, it is assessed to what extent the patient participates as an actor in their treatment process, and the information they have about their illness and the treatment they are receiving. The patient must be an active part in his healing process and there must be a deliberative process in which he is guided by the medical staff in the choice of his treatment, taking into account the ethical principles of the patient and the health personnel.